Rehabilitation After Surgical Treatment of Pectoralis Major Rupture in a CrossFit® Practitioner: A Case Report - Lucas Gomes da Silva; Rafael Marques Ferrer; José Roberto de Souza Jr.; Mauro E.C. Gracitelli; Leonardo Luiz Barretti Secchi (International Journal of Sports Physical Therapy)
# Background and Purpose